2007
DOI: 10.1177/0363546506296737
|View full text |Cite
|
Sign up to set email alerts
|

Ulnar Collateral Ligament Reconstruction in Major League Baseball Pitchers

Abstract: Most major league pitchers return from ulnar collateral ligament reconstruction by the second season after surgery with no statistical change in mean innings pitched, earned run average, or walks and hits per inning pitched from preinjury levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
115
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 120 publications
(120 citation statements)
references
References 18 publications
2
115
3
Order By: Relevance
“…Similar methods of data acquisition have been used in previous studies. 2,4,7 Data frequency tables were created to show the total number of primary and revision UCL reconstructions by year. The total revision incidence, as well as revision rates by year, was calculated from these tables to evaluate any historical trends.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar methods of data acquisition have been used in previous studies. 2,4,7 Data frequency tables were created to show the total number of primary and revision UCL reconstructions by year. The total revision incidence, as well as revision rates by year, was calculated from these tables to evaluate any historical trends.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, most MLB pitchers were observed to return to previous levels of performance within 2 seasons following primary UCL reconstruction. 2 Erickson et al 3 also reported a high incidence of return to play among MLB pitchers who had undergone UCL reconstruction and a subsequent rise in performance metrics when compared against demographic-matched controls.…”
mentioning
confidence: 98%
“…Little is known about postoperative pitching performance among pitchers who return to MLB play. Performance outcomes have been described in MLB pitchers who have undergone repair of the ulnar collateralligament 8 and repair of isolated glenoid labral injuries. 9 Therefore, the purpose of our study was to describe pitching performance outcomes in MLB players who needed surgery to treat RCTs and to compare performance variables and return to play between these athletes and a randomly selected cohort of MLB players.…”
mentioning
confidence: 99%
“…Whether owing to greater motivation, enhanced rehabilitation, or genetic superiority, elite athletes may be more likely to return to competition than their lessgifted colleagues. 3,16 There are several legitimate and complementary ways to report recovery in competitive athletes, including the time required to regain competitive form, 7,8 the ability to return to the previous level of competition, 1,6,8,17 performance statistics that reflect the reacquisition of sportspecific skills, 8,13,17 the risk of reinjury, 21 the level of residual symptoms and limitations as measured with a specialized outcomes instrument, 11 and the subsequent duration of an athlete's playing career. 4,5 The time that any athlete spends at the pinnacle of his performing ability may be very brief, so an acutely injured professional may initially focus upon recovering quickly and regaining his preinjury skill level before his small window of opportunity closes forever.…”
mentioning
confidence: 99%